Cardiolipin depletion‐induced changes in the Trypanosoma brucei proteome. Issue 12 (19th September 2019) - Schädeli, David; Serricchio, Mauro; Hamidane, Hisham Ben; Loffreda, Alessio; Hemphill, Andrew; Beneke, Tom; Gluenz, Eva; Graumann, Johannes; Bütikofer, Peter
Abstract : The mitochondrial signature glycerophospholipid, cardiolipin (CL), binds to transporters of the inner mitochondrial membrane and plays a central role in formation and stability of respiratory supercomplexes. Functional and structural requirement of CL for mitochondrial membrane proteins has been studied in vitro using purified reconstituted proteins or in CL synthesis knockout cells that are viable under specific growth conditions. However, no information is available on mitochondrial function, protein stability, or expression levels in cells during CL depletion. In contrast to yeast and mammalian cells, CL synthesis is essential in Trypanosoma brucei. By stable isotope labeling with amino acids in cell culture and mass spectrometry, we analyzed protein levels in T. brucei procyclic forms at different time points during depletion of CL using tightly controllable conditional CL synthase knockout mutants and identified a set of novel CL‐dependent proteins (CLDPs) with unknown functions. Depletion of individual CLDPs using knockout or knockdown technologies showed that although CL synthesis is essential, expression of a given CLDP is not. In addition, ablation of CL synthesis leads to respiratory supercomplex instability and altered mitochondrial ultrastructure and function. Our findings suggest that CL may bind to and affect many more proteins in eukaryotes than previously thought.—Schädeli, D., Serricchio, M., Ben Hamidane, H., Loffreda, A., Hemphill, A., Beneke, T., Gluenz, E., Graumann, J., Bütikofer, P. Cardiolipin depletion‐induced changes in the Trypanosoma brucei proteome. FASEB J. 33, 13161–13175 (2019). www.fasebj.org